2002
DOI: 10.1016/s0168-8278(02)80422-6
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year incidence of HCV infection in northern Italy and frequency of spontaneous viral clearance

Abstract: Background: Little is known of the incidence of hepatitis C virus (HCV) infection, and the frequency of spontaneous viral clearance in the general population is unknown. We conducted an epidemiological study in two Apennine towns in northern Italy. Methods: Anti-HCV (ELISA and RIBA third generation) and HCV-RNA by polymerase chain reaction were tested in thawed sera from an adult general population of Loiano-Monghidoro in 1986 and 1996, obtained in the context of the MICOL (Multicenter Italian Study on Choleli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 4 publications
3
25
3
1
Order By: Relevance
“…In contrast a study was conduct in north Italy reported 67.62% of the patients had normal ALT [27]. Our result may be due to the patients had no commitment with the prescriptive antiviral drugs.…”
Section: Liver Transferase (Alt and Ast)contrasting
confidence: 70%
“…In contrast a study was conduct in north Italy reported 67.62% of the patients had normal ALT [27]. Our result may be due to the patients had no commitment with the prescriptive antiviral drugs.…”
Section: Liver Transferase (Alt and Ast)contrasting
confidence: 70%
“…The spontaneous clearance of HCV in 17% of untreated subjects found positive for anti-HCV and HCV RNA in an open population study has ben reported 18 and cross-sectional surveys on HCV infection indicate that only a proportion of anti-HCV positive subjects show signs of viral replication. [18][19][20] This is relevant also in high-risk populations, since it has been shown that a previous humoral response towards HCV, albeit not protective against reinfections, may lead to a shorter course of active infection with clearance of RNA within 150 days in the majority of reinfected subjects. 21 Determining the presence of an active HCV infection is clinically relevant, and in this respect the automated assay for HCV Ag evaluated in this study is more suitable than HCV-RNA methods, that are more expensive and require a dedicated sample and skilled personnel.…”
Section: Discussionmentioning
confidence: 99%
“…New cases have been decreased through the detection of blood donors since 1990 s, but part of patients would progress to chronic hepatitis, liver cirrhosis and hepatocellular carcinoma. Although there are many reports on this aspect in Western countries [9][10][11][12][13] , few similar researches have been carried out in China. So it is very necessary to summarize the natural outcome of HCV in China.…”
Section: Discussionmentioning
confidence: 99%